Evaporation of Droplet with and without laser excitation - Choo, Shun Qiang. (2013)
Experiments on hanging water and ethanol droplet evaporation on a thermocouple with and without laser excitation demonstrate that the surface tension affects the rate of evaporation and the temperature increase. In the absence of laser excitation, water and ethanol droplets are subjected to evaporation under various room temperatures. The results obtained conclude that the increase in room temperature will bring about an increase in evaporation rate.